Development of Smart and Portable Controllable Syringe Pump System for Medical Applications - Basem Abu Zneid; Mays Nofal; Wael A. Salah; Amir Abu_Al_Aish (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Due to their efficiency and adaptability, automated applications are consistently gaining popularity around the world. Robotics and their applications as used in a variety of commonplace industries, such as medical applications, require a high level of precision and accuracy. This can be achieved by utilizing automated applications. In this work, the development and design of a regulated injection pump is detailed. The developed prototype is a type of robot that can be utilized in hospitals and other medical facilities. The proposed design is used to pump specific liquid volumes as specified by the user. During liquid pumping, both the fluid’s volume and velocity can be manipulated. Implementation of the proposed system required the development of a complete mechanical system and a controller. The proposed system was implemented successfully, and its operation was deemed satisfactory. According to the results, the accuracy of the system was also satisfactory. Using a flow sensor, the reference value and the measured value acquired from the designed device were compared. Compared to similar devices, the proposed system demonstrated exceptional precision, with an average error rate of less than 1.5%. The proposed model has the advantages of using a commercially available injection syringe and being significantly less expensive than similar devices on the market.